Navarro sanitary landfill: the environmental damage caused by the cities of Cali, Jamundí and Yumbo (2020)
This article warns about the environmental effects of an ecological disaster that occurred in the sanitary landfill of Navarro and the Cauca River, in Cali. With the help of some specialists in the environmental part of the subsoil of the sanitary landfill, it was revealed that a large part of the degraded waste had been absorbed by the earth. This also caused these fluids to seep into the Cauca River, leaving its water contaminated.